2005
DOI: 10.1021/ac050425+
|View full text |Cite
|
Sign up to set email alerts
|

On-Line Coupling of Gel Electrophoresis and Inductively Coupled Plasma-Sector Field-Mass Spectrometry for the Determination of dsDNA Fragments

Abstract: The on-line coupling of gel electrophoresis (GE) and inductively coupled plasma-mass spectrometry (ICPMS) is described for the first time. The new method combines the separation power of GE for large biomolecules and the high sensitivity and elemental selectivity of ICPMS. This coupling has been achieved by means of gels housed in glass tubes (length 2.5-20 cm; i.d. 0.5-5 mm). The gel is fixed by glass frits permeable for the analytes. After the electrophoretic separation at voltages up to 500 V, the analytes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
38
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 16 publications
0
38
0
Order By: Relevance
“…With a detection unit consisting of a laser emitting at 266 nm and a DAD recording from 500 to 700 nm coupled to an ITP unit, the recording of emission spectra was possible for migrating CdTe nanoparticles coated with mercaptoacetic acid [99]. Selective and sensitive detection of metal and semiconductor nanoparticles is also possible by ICP-MS. To this end, Brüchert and Bettmer [100] and Helfrich et al [101] developed a device that allows the on-line coupling of microcolumn gel electrophoresis with ICP-MS. The authors demonstrated the size-selective separation of gold nanoparticles (mean diameter 5 and 20 nm, agarose gel, 2.0%) coupled on-line with element-selective detection.…”
Section: Selective Detectionmentioning
confidence: 99%
“…With a detection unit consisting of a laser emitting at 266 nm and a DAD recording from 500 to 700 nm coupled to an ITP unit, the recording of emission spectra was possible for migrating CdTe nanoparticles coated with mercaptoacetic acid [99]. Selective and sensitive detection of metal and semiconductor nanoparticles is also possible by ICP-MS. To this end, Brüchert and Bettmer [100] and Helfrich et al [101] developed a device that allows the on-line coupling of microcolumn gel electrophoresis with ICP-MS. The authors demonstrated the size-selective separation of gold nanoparticles (mean diameter 5 and 20 nm, agarose gel, 2.0%) coupled on-line with element-selective detection.…”
Section: Selective Detectionmentioning
confidence: 99%
“…The µLC-ICP-MS (pioneering work described by Lehmann and co-workers [32] The recently introduced on-line coupling of GE to ICP-MS is a further development and was first described by Brüchert and Bettmer [35] for the determination of dsDNA fragments. More recently, it has been reported for several applications including: size characterization of gold nano particles [36], detection of iron in metalloproteins [37], determination of the degree of phosphorylation in casein [38], and for iodide and iodate determination in aerosols [39].…”
Section: Introductionmentioning
confidence: 99%
“…17 Recently Brüchert and Bettmer developed an interface for the online coupling of 1D slab gel electrophoresis and ICP-MS that allows the separation and quantification of DNA strands. 158 Detection limits of 1 ng DNA absolute have been achieved, which corresponds to 96 pg of phosphorus. In comparison to CE, relatively poor separation efficiency can be obtained with a 1D agarose gel, which represents the main limitation of this setup.…”
mentioning
confidence: 99%
“…195 They introduced a new interface comparable to those described by Brüchert and Bettmer for on-line isotope-dilution GE-ICP-MS. Iron-sulfur ratios were measured to monitor possible iron loss during the sodium dodecyl sulfatepolyacrylamide gel electrophoresis separation. 158,195,196 In summary it is fair to say that most examples regarding the absolute quantification of a biomolecule via its sulfur content have been carried out with proteins. In consequence, currently only protein samples of low complexity can be quantified with a sulfur-based approach due to the problems related to the chromatographic separation of intact proteins.…”
mentioning
confidence: 99%